Efektifitas Inquiry-Based Learning Metode Percobaan Berbantu Panduan Digital Mata Pelajaran IPA Sekolah Dasar : Dampak Hasil Belajar dan Kecakapan Berpikir Kritis - Ahmad Syukur; Nur Fajrie; Irfai Fathurohman (Universitas Muria Kudus, 2024)
The significance on the implementation of inquiry-based learning using digital experiment guidance on learning outcomes and students' critical thinking is the aim of the research that being carried out. 2 cycles of classroom action research is the research design used. 30 participants (19 boys and 11 girls) in class V of SD N 2 Kalipucangwetan, Welahan, Jepara academic year 2023/2024 were participants in the research. Summative test, formative test, and observation were the instruments of the research. Class actions influenced increasing the average score of learning outcomes respectively by 66.9, 68.9 and 76.2 (precycle to cycle II). The increasing of classical completeness (KK) was 57%, 67% and 83% respectively (precycle to cycle II). The. critical thinking skills average achievement score increased from 76.25 to 79.86 with 100% classical completion by the end of cycle II. The research found the significance on the implementation of the learning model.